2013
DOI: 10.1007/s12010-013-0449-y
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Chitosan-Immobilized Talaromyces thermophilus Lipase to a Batch Biodiesel Production from Waste Frying Oils

Abstract: Waste frying oil, which not only harms people's health but also causes environmental pollution, can be a good alternative to partially substitute petroleum diesel through transesterification reaction. This oil contained 8.8 % of free fatty acids, which cause a problem in a base-catalyzed process. In this study, synthesis of biodiesel was efficiently catalyzed by the covalently immobilized Talaromyces thermophilus lipase and allowed bioconversion yield up to 92 % after 24 h of reaction time. The optimal molar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 52 publications
1
11
0
1
Order By: Relevance
“…). When exceeding a molar ratio of 8:1, the rate of methanolysis obtained with the free enzyme becomes significantly lower than with immobilized lipase, probably owing to the direct contact between methanol droplets and lipase molecules and thereby more strongly deactivating the free enzyme (Romdhane et al, ). In addition, the immobilized lipase gave a higher FAME content as compared with its nonimmobilized counterpart for all substrate ratios.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…). When exceeding a molar ratio of 8:1, the rate of methanolysis obtained with the free enzyme becomes significantly lower than with immobilized lipase, probably owing to the direct contact between methanol droplets and lipase molecules and thereby more strongly deactivating the free enzyme (Romdhane et al, ). In addition, the immobilized lipase gave a higher FAME content as compared with its nonimmobilized counterpart for all substrate ratios.…”
Section: Resultsmentioning
confidence: 99%
“…At the end of each batch, the immobilized lipase was recovered by centrifugation. The immobilized lipase was washed with tert ‐butanol to remove any substrate or product (eventually glycerol) retained in the matrix (Romdhane et al, ). After that, it was vacuum filtered and placed in a desiccator containing silica gel.…”
Section: Methodsmentioning
confidence: 99%
“…F18 showed an activity level of 1.04 U/ml. Romdhane et al (2013) obtained enzymatic activity of 9.8 U/ml for the purified lipase produced by the fungus T. thermophilus. Thus, the endophytic fungus Talaromyces sp.…”
Section: Enzyme Productionmentioning
confidence: 99%
“…9092 While these immobilized enzymes show enhanced activity and allow for reuse, studies have shown that the support material can further improve the activity of commercially available enzymes through enzyme–material interactions. 93,94 Recent research on immobilized lipases for waste oil valorization commonly explores silica supports, 86,9496 resins, 97100 biological supports (e.g., chitosan), 101,102 and nanomaterials. 103107
Fig.
…”
Section: Applications Of Immobilized Enzymes In Food Waste Stream Valmentioning
confidence: 99%